Internet Science Second International Conference, INSCI 2015, Brussels, Belgium, May 27-29, 2015, Proceedings - Tiropanis, Thanassis; Vakali, Athena; Sartori, Laura; Burnap, Pete (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the proceedings of the Second International Conference on Internet Science, INSCIE 2015, held in Brussels, Belgium, in May 2015. The 10 papers presented were carefully reviewed and selected for inclusion in this volume. They were organized in topical sections named: internet and society; internet and governance; and internet and innovation.